The Impact of Vocational High School Collaboration with Creative Industries on Graduate Job Readiness in the Digital Era - Nur Rahmat Wibowo (Didaktika: Jurnal Kependidikan, 2025)
In the digital era, collaboration between Vocational High Schools and the creative industry is an important factor in preparing graduates who are ready to work. This study aims to analyze the impact of cooperation between SMKN 3 Yogyakarta and the creative industry on students' job readiness, with a focus on technical skills, soft skills, digital technology adaptation, and readiness to enter the world of work. The research method used was quantitative with a case study approach at SMKN 3 Yogyakarta, involving 45 respondents consisting of students, teachers, and industry representatives. Data collection was carried out through a survey with a Likert scale and analyzed using a simple linear regression test and a determination coefficient. The results of the study show that this collaboration has a significant impact on students' job readiness, with the improvement of technical skills and adaptation to digital technology which is considered very good by students and teachers. However, the industry still considers that there is a gap in professionalism and understanding of students' work culture. The determination coefficient (R²) value of 0.78 indicates that this collaboration explains most of the variability of students' work readiness. Thus, this study confirms that the cooperation between vocational schools and the creative industry is an effective strategy in increasing students' job readiness, although improvements are still needed in soft skills training and industrial professionalism.